4. NEW FUNGAL INFECTIONS DIAGNOSIS: REVIEW (Vietnam Journal of Community Medicine, 2025)
Currently, there are numerous methods available for diagnosing fungal infections that have been developed and implemented in hospitals. However, each method has its own advantages and disadvantages regarding sensitivity, accuracy, time, and so on. To improve the accuracy and speed of diagnosing fungal infections, several new methods are being tested by researchers on clinical samples. Most of these improved methods operate independently of pathogen isolation, meaning that diagnosis transitions from being considered definitive to being probabilistic. Although there is the advantage of not relying on culture, most methods lack standardization. This review aims to examine the methods for diagnosing systemic fungal infections, from diagnostic classification through methods regarded as "gold standards" to molecular techniques currently in use, and finally discuss some more future-oriented approaches.
Keywords: Candida; fungal; diagnostic test